Resolva a imagem a seguir
Anexos:
![](https://pt-static.z-dn.net/files/d6b/bf06f47047081ba52f541e5a366e1168.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
25.87
Explicação passo-a-passo:
X-1=x+y-6
X-x-1+6=y
Y=5
X+y=6
X+5=6
X=1
(1,5)
X-1=x-3y-9
X-x+9=-3y
Y=-3
X-3y=9
X-3(-3)=9
X+9=9
X=0
(0,-3)
X+y-6=x-3y-9
X-6-x+9=-3y-y
3=-4y
Y=-3/4
X+(-3/4)=6
X=+3/4+6
X=27/4
(27/4,-3/4)
1____5__1 |1_____5
0____-3__1 | 0____-3
27/4_-¾__1 | 27/4_-¾
51,75*½=>25.87
um8bemyniga:
ali na parte do X-1=x-3y-9
Perguntas interessantes
Matemática,
10 meses atrás
História,
10 meses atrás
Biologia,
10 meses atrás
História,
1 ano atrás
Biologia,
1 ano atrás